Passive sampling: an effective method for monitoring seasonal and spatial variability of dissolved hydrophobic organic contaminants and metals in the Danube river - Vrana, Branislav; Klučárová, Veronika; Benická, Eva; Abou-Mrad, Ninette; Amdany, Robert; Horáková, Soňa; Draxler, Astrid; Humer, Franko; Gans, Oliver (Environmental pollution (1987), 2014)
Application of passive samplers is demonstrated for assessment of temporal and spatial trends of dissolved polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs) and priority metals in the middle stretch of the Danube river. Free dissolved concentrations of PAHs, measured using SPMD samplers, ranged from 5 to 72 ng L(-1). Dissolved PCBs in water were very low and they ranged from 5 to 16 pg L(-1). Concentration of mercury, cadmium, lead and nickel, measured using DGT samplers, were relatively constant along the monitored Danube stretch and in the range <0.1, <1-20, 18-74, and 173-544 ng L(-1), respectively. Concentrations of PAHs decreased with increasing temperature, which reflects the seasonality in emissions to water. This has an implication for the design of future monitoring programs aimed at assessment of long term trends. For such analysis time series should be constructed of data from samples collected always in the same season of the year.
Keywords: hydrofobní a hydrofilní interakce; řeky; Seasons; roční období; Environmental Monitoring; Metals; Rivers; Hydrophobic and Hydrophilic Interactions; Polycyclic Aromatic Hydrocarbons; Polychlorinated Biphenyls; polycyklické aromatické uhlovodíky; monitorování životního prostředí; polychlorované bifenyly; kovy; Water Pollutants, Chemical; chemické látky znečišťující vodu